Simulating range oversampled Doppler radar profiles of inhomogeneous targets - Schutgens, N (2008)
A new technique for generating range oversampled profiles of Doppler radar signals that have been backscattered by distributed targets is presented in this paper. The technique was developed for spaceborne cloud radars, but it can just as well be used for ground-based precipitation or wind-profiling radars. The technique is more versatile than the traditional inverse FFT technique and faster than the individual hydrometeor simulation (Monte Carlo) technique. Doppler radar signals from backscattering hydrometeors are essentially correlated stochastic variables. The technique uses an accurate description of covariances between voltages measured for different pulses and at different positions (range gates) along a profile. A matrix formalism is developed to subsequently transform uncorrelated Gaussian noise into correlated receiver voltages with the appropriate covariances. In particular, the new technique deals with target variability in a physically consistent manner, accounting for the effects of inhomogeneity both within the instantaneous field of view and between subsequent pulses. The new technique is showcased with examples of simulated 95-GHz Doppler radar observations by the Earth Clouds, Aerosols and Radiation Explorer (EarthCARE) space mission. © 2008 American Meteorological Society.